Monetary Emissions Trading Mechanisms - Cyril Monnet; Ted Temzelides (Center for Economic Studies and ifo Institute (CESifo), 2014)
Emissions trading mechanisms have been proposed, and in some cases implemented, as a tool to reduce pollution. We explore the similarities between emission-trading mechanisms and monetary mechanisms. Both attempt to implement desirable allocations under various frictions, including risk and private information. In addition, implementation relies on the issue and trading of objects whose value is at least partially determined by expectations, namely money and permits, respectively. We use insights from dynamic mechanism design in monetary economics to derive properties of dynamic emissions trading mechanisms. At the optimum, the price of permits must increase over time. Efficient tax policies are state-contingent, and there is an equivalence between state-contingent taxes and emissions trading. Restrictions resulting from the money-like feature of permits can break this equivalence when there is endogenous progress in clean technologies. These restrictions must be taken into consideration in actual policy implementation.
Keywords: A10; 330